2017
DOI: 10.1002/pola.28502
|View full text |Cite
|
Sign up to set email alerts
|

Oligo- and poly(fullerene)s for photovoltaic applications: Modeled electronic behaviors and synthesis

Abstract: The atom transfer radical addition polymerization (ATRAP) of fullerene to give poly(fullerene)s (PFs) for organic electronics is explored. Quantum chemistry maps the expected electronic behavior of PFs with respect to common electron acceptors, namely fullerene, phenyl‐C61‐butyric acid methyl ester and its bis‐adduct, and mono‐ and bis‐indine‐fullerene derivatives. Surprisingly, it is found that PFs should demonstrate electron affinities and LUMO energy levels closer to the bis‐derivatives than the mono‐adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The samples that were used in this study are the same as those characterized (GPC, NMR, UV–visible, cyclic voltammetry, etc.) in detail in reference , and accordingly the same code for each structure is used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples that were used in this study are the same as those characterized (GPC, NMR, UV–visible, cyclic voltammetry, etc.) in detail in reference , and accordingly the same code for each structure is used.…”
Section: Resultsmentioning
confidence: 99%
“…Steric exclusion created by the first pair of additions, coupled with a favorable ratio of reagents, tends to limit the attack of more comonomers to the C 60 , making it possible to form linear oligomers and polymers. Further details are given in reference .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our own work, we have found that by using fullerene as a comonomer in alternating main‐chain polymers, it is possible to raise the position of the LUMO by around 0.5 eV with respect to PCBM by way of the type of polyaddition and comonomer used, as shown in Fig. 14 77–81 . However, these variations still remain little in comparison to the so‐called non‐fullerene acceptors.…”
Section: The Active Layermentioning
confidence: 97%
“…Prior methods included Diels–Alder chemistry, methano‐bridges and an elegant tether‐directed pre‐modification of C 60 , but these also gave crosslinking, intractable products or required multi‐step preparative chemistry, respectively. An attempt to resolve this was made using atom transfer radical addition polymerization as the reaction is based on radical bis‐additions around just one C 60 1,4‐phenylic ring . One disadvantage of this system, though, was the high amounts of CuBr required, leading to metal impurities of which even trace amounts can be detrimental to device performances .…”
Section: Introductionmentioning
confidence: 99%